2019
DOI: 10.1103/physrevmaterials.3.124203
|View full text |Cite
|
Sign up to set email alerts
|

Unusual valence state in the antiperovskites Sr3SnO and Sr3PbO revealed by x-ray photoelectron spectroscopy

Abstract: The class of antiperovskite compounds A3BO (A = Ca, Sr, Ba; B = Sn, Pb) has attracted interest as a candidate 3D Dirac system with topological surface states protected by crystal symmetry. A key factor underlying the rich electronic structure of A3BO is the unusual valence state of B, i.e., a formal oxidation state of −4. Practically, it is not obvious whether anionic B can be stabilized in thin films, due to its unusual chemistry, as well as the polar surface of A3BO, which may render the growth-front surface… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
(54 reference statements)
1
13
0
Order By: Relevance
“…Importantly, many antiperovskites are stable and experimentally well studied. In particular, the compounds Ca 3 PbO, Ca 3 SnO, Sr 3 PbO, and Sr 3 SnO have been the subject of several recent experiments [40][41][42][43][44][45][46]. Thus, our results present a promising avenue to pursue experimen- tal studies of HOTIs, for which very few other candidates have been identified.…”
Section: Discussionmentioning
confidence: 76%
“…Importantly, many antiperovskites are stable and experimentally well studied. In particular, the compounds Ca 3 PbO, Ca 3 SnO, Sr 3 PbO, and Sr 3 SnO have been the subject of several recent experiments [40][41][42][43][44][45][46]. Thus, our results present a promising avenue to pursue experimen- tal studies of HOTIs, for which very few other candidates have been identified.…”
Section: Discussionmentioning
confidence: 76%
“…Detailed growth procedures, as well as film characterization via x-ray diffraction (XRD), low-energy electron diffraction and x-ray photoelectron spectroscopy, can be found in Refs. [39,40].…”
Section: Methodsmentioning
confidence: 99%
“…Line-cut analysis [Fig.2(c)] reveals step edges with heights corresponding to integer multiples of the unit cell (UC), roughly 0.51 nm. We were unable to resolve an atomic lattice, likely due to complications arising from surface polarity and valence instability[40].…”
mentioning
confidence: 99%
“…ABX 3 perovskites, as the largest family of crystalline materials, also have their counterpart antistructures, A 3 BX antiperovskites 7 . In contrast to the perovskite compounds constructed by the ionic bonds of constituent elements in stable valence states, the antiperovskites have mixed bonding characters with ionic, covalent, and metallic bonds in unusual valence states 8 . However, oxide antiperovskites (A 3 BO), antistructures of common oxide perovskites (ABO 3 ), are hardly stabilized in ambient conditions as oxygen tends to form ionic bonds with counter-cationic A and B elements due to its large ionicity 9 .…”
Section: Introductionmentioning
confidence: 99%